The effects of MiFID II on sell-side analysts, buy-side analysts, and firms - FANG, Bingxu (Institutional Knowledge at Singapore Management University, 2020)
This paper provides early but broad empirical evidence on MiFID II, which requires investment firms to unbundle investment research from other costs they charge to clients. Employing difference-in-differences matched-sample research designs with firm fixed effects, we find a decrease in the number of sell-side analysts covering European firms after MiFID II implementation, particularly for firms that are less important to the sell-side. However, research quality improves; specifically, individual analyst forecasts are more accurate and stock recommendations garner greater market reactions. In addition, sell-side analysts seem to cater more to the buy-side after MiFID II by providing industry recommendations along with stock recommendations. Importantly, we predict and find evidence that buy-side investment firms turn to more inhouse research after MiFID II implementation. Equally interesting, buy-side analysts increase their participation and engagement in earnings conference calls, compared to the control group. We find some evidence that stock-market liquidity decreases post MiFID II.